Meningioma with rosettes: A rare morphologic pattern. Issue 2 (2nd December 2019) - Poyuran, Rajalakshmi; Thomas, Bejoy; Abraham, Mathew; Narasimhaiah, Deepti
Abstract : We describe a case of WHO grade I transitional meningioma with rosettes in a 68‐year‐old woman. The rosettes were composed of meningothelial cells arranged around dense collagenous cores. Even though the presence of rosettes in tumors of the brain and spinal cord is an indication of neuronal or ependymal differentiation, they are also known to occur in tumors of other lineages. Rosette is an uncommon morphological pattern in meningiomas, with only few cases reported in the literature.